Scope of constructivism as a paradigm in research - Valenciano Canet, Grettel (2022)
In this essay reflects on the epistemological, theoretical, and methodological referents of the constructivist research paradigm with the aim of being applied in the social sciences.  From this point of view, it is intended to expose the conception of this implicit body of beliefs, its ontological, axiological, methodological, and theoretical premises in relation to social reality.  On the other hand, the basic principles common to the various currents of constructivist thought are identified, to characterize and substantiate it. The theoretical, methodological, and practical implications of assuming it in scientific research, as well as its reliability and validity as a research paradigm, are also sought.